2018
DOI: 10.1002/asia.201701561
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt‐Doped Perovskite‐Type Oxide LaMnO3 as Bifunctional Oxygen Catalysts for Hybrid Lithium–Oxygen Batteries

Abstract: Perovskite-type oxides based on rare-earth metals containing lanthanum manganate are promising catalysts for the oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) in alkaline electrolyte. Perovskite-type LaMnO shows excellent ORR performance, but poor OER activity. To improve the OER performance of LaMnO , the element cobalt is doped into perovskite-type LaMnO through a sol-gel method followed by a calcination process. To assess electrocatalytic activities for the ORR and OER, a series of LaM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(41 citation statements)
references
References 46 publications
2
39
0
Order By: Relevance
“…Porous structures are desirable for electrocatalytic applications because they facilitate the diffusion of electrolyte ions and solvents into the material, thus providing more active catalytic sites. In this context, LaMn1-xCoxO3 perovskites are expected to present an appropriate porosity due to the calcination process employed during the synthesis, which removes both EDTA and citric acid from the structure and promotes the thermal decomposition of nitrate [45]. The surface morphology of a set of LaMn1-xCoxO3 perovskites, with x = 0, 0.2, 0.8 and 1, was examined by SEM microscopy and the results are presented in Fig.…”
Section: Surface Morphology Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Porous structures are desirable for electrocatalytic applications because they facilitate the diffusion of electrolyte ions and solvents into the material, thus providing more active catalytic sites. In this context, LaMn1-xCoxO3 perovskites are expected to present an appropriate porosity due to the calcination process employed during the synthesis, which removes both EDTA and citric acid from the structure and promotes the thermal decomposition of nitrate [45]. The surface morphology of a set of LaMn1-xCoxO3 perovskites, with x = 0, 0.2, 0.8 and 1, was examined by SEM microscopy and the results are presented in Fig.…”
Section: Surface Morphology Analysismentioning
confidence: 99%
“…Besides, the produced Mn 4+ species provides higher oxidation capability than the original Mn 3+ . On the contrary, Liu et al [39] reported that the catalytic activity of the undoped perovskite is higher and, for similar cobalt and manganese content, such catalytic activity decreases drastically due to the alterations induced in the crystal structure by the smaller cation. Nevertheless, they found that the activity toward OER enhances after the introduction of cobalt and reported that LaMn0.7Co0.3O3 perovskite shows the best response toward OER, so this material was suggested as a promising bifunctional electrocatalyst.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Oxygen reduction and evolution reactions (ORR and OER) are cornerstone reactions for electrochemical conversions between chemical and electronic energy [4][5][6]. For example, ORR wieldy exists in fuel cells and the discharge process of metal-air batteries [7,8], while OER is involved in electrolytic water splitting and metal-air batteries during the charge process [9,10]. However, the state-of-the-art noble metal (oxide) electrocatalysts, such as Pt-based materials for ORR and Ir-and Ru-based materials for OER, are significantly limited by the high cost, scarce resource, and low bifunctional activity [11].…”
Section: Introductionmentioning
confidence: 99%
“…The ORR activity of the crystalline Pr 6 O 11 sample was better than that of the as-prepared one ( Figure 9A), as clearly revealed when directly superposing the two sets of data on the same axes ( Figure 9B). While the onset potential value (E onset = 0.835 V vs RHE, in the average for such class of materials [46,[75][76][77][78][79][80][81], although in these papers, the materials were tested with carbon as electron-conductive additive) was barely changed compared to the amorphous sample, the limiting current plateaus were better defined. However, they still do not match the expected values for a 4-electron ORR, by a factor ca.…”
Section: Pr6o11 Sintered (Crystalline)mentioning
confidence: 97%